1974
DOI: 10.1084/jem.140.3.660
|View full text |Cite
|
Sign up to set email alerts
|

Specific Positive Selection of Lymphocytes Reactive to Strong Histocompatibility Antigens

Abstract: The population of thymus-derlved (T) lymphocytes reactive to strong histocompatibility (H) 1 alloantigens (HARC) is peculiar in two respects in comparison to lymphocytes~responsive to other antigens: first, the T cells reactive to any given strong H antigen outnumber by two to three orders of magnitude the T cells responsive to more conventional antigens (1-3); and secondly, the frequency of HARC to a given H alloanfigen is not increased as a consequence of immunization in vivo (4-6). Just how fundamental thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…It is well known that a high percentage of T lymphocytes in a normal individual is precommitted to react across the major histocompatibility barrier of the species as measured by activation of function in mixed leukocyte cultures or graft-versus-host reactions (4)(5)(6). Recently, we have been able to confirm the unusual high figures in normal lymphocytes using specific anti-idiotypic antibodies (7).…”
supporting
confidence: 67%
“…It is well known that a high percentage of T lymphocytes in a normal individual is precommitted to react across the major histocompatibility barrier of the species as measured by activation of function in mixed leukocyte cultures or graft-versus-host reactions (4)(5)(6). Recently, we have been able to confirm the unusual high figures in normal lymphocytes using specific anti-idiotypic antibodies (7).…”
supporting
confidence: 67%
“…Thus these experiments clearly show that the requirements for inducing T killer cell proliferation and for killing are different. Howard & Wilson (1974) recently reported that rat lymphocytes, reactive to strong histocompatibility antigens in vitro, if propagated in thymus-depleted animals for prolonged periods of time, not only show a strong proliferative response to the original priming alloantigens but also to others. It should be stressed, however, that this behavior of T killer cells in a secondary response appears to be different from the primary response, in that T killer cell sensitization in the primary response usually gives rise to effector cells specific for the sensitizing cells only.…”
Section: D) Specificity Of the T Killer Cellmentioning
confidence: 99%
“…The recently described "primed lymphocyte typing" (PLT) assay (2) has made it possible to determine indirectly the genetic control of xenogeneic MLC. Sensitization in a mixed lymphocyte culture positively selects for memory cells which give a rapid secondary response upon restimulation with cells from the initial stimulator (3,4). Studies in human families (2,(5)(6)(7) showed that restimulation is caused by the same LD determinants of the major histocompatibility complex (MHC) that induce primary MLC responses.…”
mentioning
confidence: 99%